ResMul - López Brugos, José Antonio; Corte, Belarmino (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
This paper describes the essential idea of RESMUL (Semantic Nets for Hypermedia). RESMUL deal to outline with a Intelligent Tutoring hypermedia environment (HIIT) foundation supported by experience and reflection about knowledge, and a representation knowledge system based on extended semantic nets, combinig both distributive and collective sets and pointing out the inheritance problem of properties. Thus, the essential structured interrelated knowledge of images, text and voice for knowledge, HCI, interfaces and hypermedia can find sound fundation. Moreover, RESMUL try to outline a method for design HIIT and Hypermedia.